LA GESTION D’ESPACEEN PEINTUREET POESIE / ŞİİR VE RESİMDE BOŞLUKLARIN ANLAMI - Fahimeh Yasin* (Folklor/Edebiyat, 2017)
“Ut pictura poesis?” Everything seems to have already been said in this famous formula of Horace. But who would think the relations between poetry and painting, to consider from the point of view of a rivalry or in the perspective of a mere imitation? To think of the relationship in terms of substitution or adequacy would be blindly look at what is being played through various connections that take place on the horizon of these two arts. Painting is even more constantly a powerful creative aliment for writers. Victor Hugo describing in Les Miserables, the battle of Waterloo composed as a painter, with the means of language. So many texts come from an image that we want to describe, where the writer tries to give an equivalent of the painting by the means of the language. One then finds oneself in an uncertain margin where literary creation is at the same time a subject of writing, an object of reflection and a starting point for an unusual use of language. To give an account of the mute speech of painters, a great challenge, is most often only within the reach of poets, who explore language in the confines of silence. How, in the face of a canvas, will not a writer be seized by a quasi-immediate relation to the color actually received, lived, filtered by the system of language? How will poetic space allow the reader to become a spectator of the page?